Analysis of expression of cholecystokinin in dopamine cells in the ventral mesencephalon of several species and in humans with schizophrenia. - Schalling, M (1990)
The ventral mesencephalons of hamster, guinea pig, cat, monkey, and several humans with and without the diagnosis of schizophrenia were analyzed with in situ hybridization and immunohistochemistry. Extensive codistribution of cholecystokinin mRNA and tyrosine hydroxylase [L-tyrosine, tetrahydropteridine: oxygen oxidoreductase (3-hydroxylating), EC 1.14.16.2] mRNA was observed in cats and monkeys as well as in all five human subjects with the diagnosis of schizophrenia and in two out of five control brains. Double labeling revealed coexistence of the two markers in cat, monkey, and human. No cholecystokinin mRNA or cholecystokinin peptide was detected in the substantia nigra/ventral tegmental area of the hamster or guinea pig, even after acute and chronic neuroleptic treatment.